Implementasi Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Sekolah: Analisis Peran Stakeholders di Sekolah Dasar - Anak Agung Gede Agung; Chindytia; Davina Putri Ramadhani; Made Puspa Riatini; I Putu Raditha Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the role of stakeholders in improving the quality of schools through the implementation of School-Based Management (MBS) at SDN 1 Sanur, South Denpasar. The method used was qualitative descriptive through direct interviews with SDN 1 Sanur teachers and field observations. The results of the study show that the implementation of SBM at SDN 1 Sanur has gone quite well, especially in the aspects of educator management and technology-based learning. The five main stakeholder groups, namely school principals, teachers, students, parents, and the government, have carried out their respective roles in a synergistic manner. The SWOT analysis identifies key strengths in the form of strategic location, teacher competence, and participatory leadership; weaknesses in the limitations of technological infrastructure; opportunities from the Independent Curriculum policy and the development of information technology; as well as threats in the form of competition between schools and the demands of rapid digital adaptation. The evaluation of management effectiveness and efficiency shows that schools have been able to utilize resources optimally even though there is still room for improvement in learning innovations and digital-based administrative management. Strategic recommendations are prepared based on a SWOT matrix approach to encourage continuous improvement in the quality of education.